Rapid sorption of fenitrothion on didodecyldimethylammonium bromide-montmorillonite organoclay followed by the degradation into less toxic 3-methyl-4-nitrophenolate. Issue 5 (October 2020) - Oiwa, Mako; Yamaguchi, Kaho; Hayashi, Hideo; Saitoh, Tohru
Graphical abstract: Highlights: Fenitrothion in water was rapidly sorbed onto dialkylated surfactant-modified organoclay. Sorbed fenitrothion degraded into less toxic 3-methyl-4-nitropheol under mild conditions. Catalytic ability occurred by catalytic functions of surfactant assemblies and clay surfaces. Continuous treatment was successfully demonstrated by using organoclay-packed column. Abstract: Didodecyldimethylammonium bromide (DDAB)-modified montmorillonite (MT) organoclay was used for the sorption and degradation of an organophosphate pesticide, fenitrothion, in water. The degree of sorption increased by the modification of MT with DDAB, because of the formation of hydrophobic DDAB assemblies for the sorption of hydrophobic fenitrothion. Fenitrothion ([M + 1] = 278) sorbed on the organoclay rapidly converted to the degraded product anion ([M] = 262) followed by the further degradation into 3-methyl-4-nitrophenol ([M-1] = 152). The activation energy for the first-order reaction of the primary degradation of fenitrothion (79.9 kJ mol -1 ) in the organoclay was lower than the value (94.1 kJ mol -1 ) in water. Organoclay-mediated catalytic activity expressed over a wide pH region (pH 5-9), being advantageous for the application to different wastewaters and environmental waters. Continuous sorption and degradation of fenitrothion in contaminated water was examined by using a laboratory-scale organoclay-packed column. Fenitrothion-free effluent containing its degraded product, 3-methyl-4-nitrophenol, having lower toxicity to aquatic organisms outflowed from the bottom of the column. These results strongly suggests the usefulness of DDAB-MT organoclay as a barrier material for diffusion control of organophosphate pesticides.